Ground Pressure under Mining Ore Bodies of Different Angles Based on Physical Simulation - Xiaoshuang Li; Jian Song (Shock and Vibration)
Ground pressure characteristics of the ore body and the overburden deformation of the stope depend highly on the combined influence of geological conditions and mining disturbance. The ore body inclination, as a natural geological factor, has a nonnegligible effect on the underground mining. The ore angle plays a great role in the stress distribution of the overlying rock layer, resulting in the movement and destruction of the rock layer. The variation of the ore angle dominates the stress distribution of the overburden rock, the forms of movement, destruction, and the surface moving basin. Here, taking the geological mining conditions of the deep ore body mining in Jinning Phosphate Mine as the engineering background, we adopt a similar material ratio scheme of each rock layer in the mining area via the similarity theory and the principle of orthogonal experiment. We conduct systematic study on the strata movement, mining failure characteristics, and movement of the overlying rock in stope using a similar simulation test under two different ore angles of 20° and 50°. We found that, as the ore body inclination increases from 20° to 50°, the overburden unloading area of the stope extending to the deep part of the rock layer in the vertical direction is more obvious and its shape is more asymmetric about the stope center. The unloading area is more concentrated in the middle and upper part of the stope, while the upward development trend is more obvious. The relevant results can provide a certain reference for the underground mining of the mines and those with similar conditions.